The effects of rest intervals on jumping performance: A meta-analysis on post-activation potentiation studies - Gouvêa, A. L.; Fernandes, I. A.; César, E. P.; Barbosa Silva, W. A.; Chagas Gomes, P. S. (Journal of Sports Sciences, 2013)
The purpose of this meta-analytic review was to examine the extent and quality of research on the post-activation potentiation acute effect of rest interval manipulation on jumping performance. This manuscript adopted the recommendations from the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement. Criteria eligibility included crossover, randomised, non-randomised and counterbalanced studies that observed the voluntary muscle action-induced post-activation potentiation on jumping performance. Fourteen studies selected by two independent raters were included in the analysis. The rest intervals involved ranges including 0-3, 4-7, 8-12 and =16 min. The results demonstrated medium effect sizes for rest intervals 0-3 and 8-12 min (-0.25, Confidence Interval (CI): -0.51 to 0.01 for 0-3 min; 0.24, CI: -0.02 to 0.49 for 8-12 min) and a small effect for other ranges (0.15, CI: -0.08 to 0.38 for 4-7 min; 0.07, CI: -0.21 to 0.24 for =16 min). There was no evidence of heterogeneity for sub-groups (I 2 = 0%; P < 0.001) and no indication of publication bias (Egger`s test, P = 0.179). While a rest interval of 0-3 min induced a detrimental effect on jump performance, the range including 8-12 min had a beneficial impact on jump height. Findings suggest that the rest interval manipulation seems to affect post-activation potentiation magnitude and jump height.